MUP232 : Intro to performance style / College of Creative Arts - UiTM, College of Creative Arts (Universiti Teknologi MARA (UiTM), 2024)
This course aims to equip students with the ability to research, identify and critically evaluate written and recorded evidence of performance issues for a specific repertoire of music. Students will be required to resolve issues of interpretation and performance practices and to articulate these issues. Perspectives offered by composers, performers and analysts will be explored and evaluated in different performance contexts.